Long-term follow up in patients with gastroesophageal reflux disease with specific emphasis on reflux symptoms, use of anti-reflux medication and anti-reflux surgery outcome: a retrospective study. (November 2013) - Van Meer, Suzanne; Bogte, Auke; Siersema, Peter D
Abstract Background. Various treatment modalities are currently being used in patients with gastroesophageal reflux disease (GERD); however, long-term outcome is not clear. The aim is to evaluate long-term results of GERD treatments with regard to reflux symptoms, use of anti-reflux medication and anti-reflux surgery outcome. Methods. Patients who had undergone 24-h pH monitoring for reflux symptoms between January 2002 and March 2012 were invited to fill out the Reflux Disease Questionnaire (RDQ) and a general questionnaire. Patients with and without anti-reflux surgery were compared using multiple linear and logistic regression models. Results. In total, 1027 of 2190 included patients (47%) returned the questionnaires. After exclusion due to predefined criteria, 477 patients were analyzed. Median total RDQ score was 18 points (10.2% symptom-free) in the conservative group (n = 304) and 10 points (31.2% symptom-free) in the surgical group (n = 173) after a mean follow up of 5.1 years. Daily proton pomp inhibitor (PPI) use was higher in the conservative group than in the surgical group (80.9% vs. 51.4%, p = 0.000). Linear regression analysis showed an association between RDQ scores and anti-reflux surgery (β = −5.477, p = 0.001) and male gender (β = −4.306, p = 0.006). Logistic regression analyses showed that daily PPI use was lower in patients who underwent anti-reflux surgery (odds ratio [OR] = 0.24, p = 0.000), while it increased with age (OR = 1.03, p = 0.000). Conclusions. There is still a high prevalence of typical reflux symptoms and daily PPI use in GERD patients after >5 years of follow up. Male patients and patients who had undergone anti-reflux surgery were more often asymptomatic. Daily PPI use was lower after anti-reflux surgery, while it increased with age.